PERKEMBANGAN PENELITIAN KARAKTERISTIK ANGGARAN TERHADAP KINERJA MANJERIAL DI INDONESIA - Ersanti Anggunan Dewi (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2022)
The purpose of this study is to describe in general about the development of budget research in Indonesia. The development of budget research in this study was analyzed using the charting the field method. A total of 23 articles on budgets from 15 accredited journals in Indonesia from 2014 to 2020 were analyzed in this study. The variables and research methods used by the researchers form the basis of classification by researchers. Of the 23 articles studied, the researchers preferred the use of quantitative methods. Multiple regression is the most dominant analysis model used in the article in this study. Based on the results of the study, (1) most studies use budget absorption as a dependent variable; and (2) organizational commitment or management and budget participation as independent variables.